Platelet rich plasma following hysteroscopic adhesolysis: a randomized clinical trial - Ahmed, Mortada E.; Amer, Mohamed I.; Ahmed, Walaa E. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Intrauterine adhesions (IUAs) is an uncommon condition that occurs after endometrial trauma, still it affects many women seeking fertility. Hystroscopic adhesolysis is the standard management procedure for IUAs, yet many concerns arise about the incidence of recurrence. This study evaluates the efficacy of Platelet rich plasma in decreasing adhesion recurrence following hystroscopic adhesolysis of severe intrauterine adhesions. Methods: A prospective randomized clinical trial held in the Endoscopy Unit of Ain Shams University Hospital, Cairo, Egypt. 160 women with grade-III intrauterine adhesions, according to American Fertility Society criteria, were randomized to either receiving 5ml platelet rich plasma injection into the uterine wall in the most affected parts of the endometrium and lining the uterine cavity by 5ml platelet rich plasma gel followed by intrauterine insertion of folley’s catheter balloon left for two weeks (study group), or only insertion of folley’s catheter balloon for two weeks with injection of placebo solution and using placebo gel (control group). Second look office hysteroscopy was performed 3 months post-operative to assess the grade of intrauterine adhesions. The primary outcome was the incidence of recurrence of intrauterine adhesions. Secondary outcomes were the post-operative improvement of menstrual duration and flow, and pregnancy rate within 1 year post-adhesolysis. Results: 70/81(86.4%) patients showed grade-I adhesions, 8/81 (9.9%) grade-II and 3/81 (3.7%) remained grade-III in the study group compared to 42/78 (53.8%) grade-I, 21/78 (26.9%) grade II and 15/78 (19.2%) grade-III in the control group (p<0.001). Conclusions: Platelet rich plasma shows better improvement of adhesion score, menses duration and menses amount following hystroscopic dissection of severe intrauterine adhesions.